Benign Joint Hypermobility Syndrome in Patients with Attention Deficit/Hyperactivity Disorders - Şebnem KOLDAŞ DOĞAN; Yasemen TANER; Deniz EVCİK1 (Archives of Rheumatology, 2011)
Objectives: In this study, we determined whether attention deficit/hyperactivity disorder (ADHD) is accompanied by benign joint hypermobility syndrome (BJHS) and evaluated the incidence of BJHS in patients with ADHD. Patients and methods: This s tudy was p erformed in the Ufuk University Faculty of Medicine, Departments of Physical Medicine and Rehabilitation and Psychiatry between November 2007 and February 2008. A total of 54 patients (45 males, 9 females; mean age 9.7±2.2 years; range 7 to 12 years) with ADHD and 36 healthy controls (19 males, 17 females; mean age 9.8±2.3 years; range 7 to 12 years) were included in the study. The sociodemographic and clinical characteristics of the individuals and the joint pain severity in the last month were recorded. Pain severity was assessed with the Faces Pain Scale-Revised (FPS-R) and the Likert Pain Scale. The joint hypermobility was evaluated by using Beighton scores. Results: Benign joint hypermobility syndrome was found in 31.5% of the patients with ADHD and 13.9% of the individuals in the control group, and the difference was statistically significant (p=0.05). There were no statistically significant differences between the groups in FPS-R or Likert Pain Scale scores (p>0.05). A statistically significant increase was observed in the Beighton total score in ADHD patients compared with the control group (p=0.004). Conclusion: The results of this study support that joint hypermobility may be associated with ADHD, and this condition should be taken into consideration in assessing the complaints of patients with ADHD-related musculoskeletal symptoms.